Documentation centres served by the DORA project in 1992 - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
-MINANDER - R.P.A. CP 527, Luanda ANGOLA -Ministry of Agriculture and Fisheries Central Farm, Cayo District Belmopan,BELIZE -Department of Agricultural Research Library Services Ministry of Agriculture PB 0033, Gaborone BOTSWANA -Central Library...